The Dream of Arcady : Place and Time in Southern Literature - MacKethan, Lucinda Hardwick (Book collections on Project MUSE., 1999)
"This is a well-organized, gracefully written account of a significant aspect of Southern fiction, and it contains information and incisive commentary that one can find nowhere else."--Thomas Daniel YoungMany southern writers imagined the South as a qualified dream of Arcady. They retained the glow of the golden land as a device to expose or rebuke, to confront or escape the complexities of the actual times in which they lived. The Dream of Arcady examines the work of post-Civil War southern writers who criticize the myth of the South as pastoral paradise. Sooner or later in all their idealized.